The drawing of the three [compact disc, unabridged] - King, Stephen, 1947- (King, Stephen, 1947- Dark tower, 2003)
Roland of Gilead, the last gunslinger, is camped at the shore of the Western Sea when he is attacked and poisoned by lobstrosities, monsters that live in the world in which Roland exists. In search of an antidote for the poison, Roland comes upon three doors to the real world, each door offering a view to the real world from behind the eyes of a different person. A heroin addict named Eddie Dean who is in trouble with drug-dealing mobsters, a schizophrenic paraplegic living a dual life as mild-mannered Odetta Holmes and dangerous Detta Walker, and a businessman and murderer named Jack Mort who killed the confused boy from Roland's past, Jake Chambers, are behind the three doors. These people form Roland's group as he continues in his pursuit of the Dark Tower.